Artesunate Suppresses Choroidal Melanoma Vasculogenic Mimicry Formation and Angiogenesis via the Wnt/CaMKII Signaling Axis - Geng, Bochao; Zhu, Yuanzhang; Yuan, Yingying; Bai, Jingyi; Dou, Zhizhi; Sui, Aihua; Luo, Wenjuan (Frontiers in Oncology, 2021)
The traditional antimalarial drug Artesunate(ART) possesses the anticancer ability and has been shown to inhibit neovascularization in multiple cancers. However, the effect of ART on choroidal melanoma neovascularization and its mechanism underlying are remaining unclarified. Here, we have demonstrated that ART not only inhibits angiogenesis but also inhibits the formation of vasculogenesis mimicry(VM) in choroidal melanoma. By the treatment of ART, Wnt5a/CaMKII pathway, which is the downstream of VEGF and closely related to endothelial cell biology was blocked in choroidal melanoma cells. What’s more, ART downregulated the expression levels of VM-related proteins vascular endothelial (VE)-cadherin and hypoxia-inducible factor (HIF)-1α. In vitro, we demonstrated that ART inhibited the proliferation, migration and invasion of OCM-1 and C918 cells. VM formation assay and Periodic acid Schiff(PAS) staining revealed that ART inhibited VM formation in choroidal melanoma. Mouse aortic ring assay and Chorio-Allantoic Membrane(CAM) assay further indicated that ART suppressed angiogenesis ex vivo and in vivo. Collectively, our results suggest that ART inhibits angiogenesis and VM formation of choroidal melanoma likely by regulating the Wnt5a/CaMK II signaling pathway, these findings further support the feasibility of artesunate for cancer therapy.